Social Values in The Taek Lauk Tradition of Sesait Village North Lombok Regency - Jamiluddin; Dea Rusuhhi Awalia Asnan Daeng (KASTA : Jurnal Ilmu Sosial, Agama, Budaya dan Terapan, 2026)
The Taek Lauk tradition practiced in Sesait Village, North Lombok, involves rituals to pray for rain and abundant resources through prayer and social solidarity. This study aims to: (1) examine the implementation of the Taek Lauq tradition and (2) identify the social values contained therein. This study uses a qualitative descriptive approach with data collection through interviews and documentation. The data were analyzed using the Miles and Huberman method, which includes reduction, presentation, and conclusion drawing. The results show that this tradition involves several stages, including preparation and implementation, which emphasize community cooperation. This tradition affirms social values such as mutual cooperation, kinship, and respect for cultural heritage. This practice continues to strengthen social cohesion and forms the basis of community culture.